Effect of High-Fat Diet upon Inflammatory Markers and Aortic Stiffening in Mice. (11th June 2014) - Santana, Andre Bento Chaves; Souza Oliveira, Thais Cristina de; Bianconi, Barbara Lobo; Barauna, Valerio Garrone; Santos, Ed Wilson Cavalcante Oliveira; Alves, Tatiana P.; Silva, Juliane Cristina S.; Fiorino, Patricia; Borelli, Primavera; Irigoyen, Maria Claudia Costa; Krieger, José Eduardo; Lacchini, Silvia
Abstract : Changes in lifestyle such as increase in high-fat food consumption are an important cause for vascular diseases. The present study aimed to investigate the involvement of ACE and TGF- β in the aorta stiffness induced by high-fat diet. C57BL/6 male mice were divided in two groups according to their diet for 8 weeks: standard diet (ST) and high-fat diet (HF). At the end of the protocol, body weight gain, adipose tissue content, serum lipids and glucose levels, and aorta morphometric and biochemical measurements were performed. Analysis of collagen fibers by picrosirius staining of aorta slices showed that HF diet promoted increase of thin (55%) and thick (100%) collagen fibers deposition and concomitant disorganization of these fibers orientations in the aorta vascular wall (50%). To unravel the mechanism involved, myeloperoxidase (MPO) and angiotensin I converting enzyme (ACE) were evaluated by protein expression and enzyme activity. HF diet increased MPO (90%) and ACE (28%) activities, as well as protein expression of ACE. TGF- β was also increased in aorta tissue of HF diet mice after 8 weeks. Altogether, we have observed that the HF diet-induced aortic stiffening may be associated with increased oxidative stress damage and activation of the RAS in vascular tissue.